Penerapan Strategi Preview, Question, Reading, Reflect, Recite, Review (Pq4r) Dalam Meningkatkan Ketrampilan Membaca Siswa Kelas 5 SD Negeri Bentak 2 Sragen Tahun Ajaran 2015/2016 - Purnomo, Trijoko, Dra.Risminawati, M.Pd (2016)
ABSTRACK Trijoko Purnomo/A510120053 Implementation Strategy Preview, Question, Read, Reflect, Recite, Review (PQ4R) Increase Reading Skills Class 5 Sd State Bentak 2 Sragen Academic Year 2015/2016. The Faculty of Education, University of Muhammadiyah Surakarta. January, 2016. Class Action Research aims to improve students' reading skills of grade V SDN snaps 2 2015/2016 academic year through a strategy Preview, Question, Reading, Reflect, Recite, Review (PQ4R). This research is a class act. The subjects of this study is the fifth grade students and teachers at SDN snapped 2. Methods of data collection using observation, interviews, documentation and tests, students of class V SDN snaps 2 2015/2016 academic year before and after the action. Data were analyzed using interactive analysis, data presentation and conclusion / verification. Based on the results of actions pre-cycle, cycle 1 and cycle 2 showed that there was increase in the skills of reading, before the action or the reading skills of students in pre-cycle still has the skills of low reading is 24% or 6 students who have reading skills are good, the first cycle the first meeting increased to 36% or 9 students. Cycle I petemua II increased again at 56% or 14 students who have good reading skills, the second cycle first meeting good reading skills, there are 18 students or 72%. Cycle II meeting II students acquire good reading skills which are 21 students or 84%. Thus it can be suggested by the strategy Preview, Question, Reading, Reflect, Recite, Review (PQ4R) can improve reading skills Keywords: Strategy Preview, Question, Reading, Reflect, Recite, Review (PQ4R) reading skills.